Current exposure of Italian women of reproductive age to PFOS and PFOA: A human biomonitoring study. (October 2015) - De Felip, Elena; Abballe, Annalisa; Albano, Fulvia Lucia; Battista, Tatiana; Carraro, Valter; Conversano, Michele; Franchini, Silva; Giambanco, Laura; Iacovella, Nicola; Ingelido, Anna Maria; Maiorana, Antonio; Maneschi, Francesco; et al.
Highlights: Largest human biomonitoring study in women of reproductive age in Italy. No differences in PFOS concentrations between urban/industrial and rural areas. Levels of PFOA higher in women residing in urban/industrial areas. A downward temporal trend in exposure is observed for both compounds. Abstract: Perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) concentrations were determined in serum samples collected in 2011–2012 from 549 nulliparous Italian women of reproductive age who resided in six different Italian Regions. Assessment of exposure to perfluorinated compounds was part of a large human biomonitoring study (Project Life Plus "Womenbiopop") that aimed at examining the exposure of women of reproductive age to priority organic pollutants. The median concentrations of PFOS and PFOA were 2.43, and 1.55 ng g −1, respectively. Significant differences in the concentrations of both compounds were observed among the six Regions. Women from central Italy had the highest levels of both compounds, followed by women from northern Italy, and southern Italy. No differences in the PFOS concentrations were found between women from urban/industrial areas and women from rural areas, whereas the levels of PFOA were significantly higher in women residing in urban/industrial areas than in women residing in rural areas. Taken together, the observed concentrations confirm that the overall exposure of the Italian population is among the lowest observed in industrialized countries. A downward temporal trend in exposure was observed for both compounds when comparing the results from the present study with those assessed in a study conducted in 2008.